# ALGEBRA

posted by .

Multiply: (K+3)/(4K-2)*(12K^2 + 2k – 4)
• 3(k+3)/(3k+2)
• 3(k+3)(2k-1)/2
• (x-5)(3x+2)
• (x-5)(12x+8)

How?
11

• ALGEBRA -

well, 12k^2+2k-4 = 2(3k+2)(2k-1)

so, we have

(k+3)/2(2k-1) * 2(3k+2)(2k-1)
now the 2(2k-1) cancels, leaving

(k+3)(3k+2)

## Similar Questions

1. ### Algebra (new one since I put "match" (bad speller)

I have a few match problems that I can't figure out. 1.solve: 3x+5=x√7 (that's a radical sign) 2.factor: (2k+3)2-(2x+3)(y-2)-20(y-2)2 (the "2" after (2k+3) ans (y-2) is suppose to be a square sign. thanks if you can help, or …
2. ### math

how do i do x2+12x+32 x2+12x = 14x+32 subtract 14x from each side 14x=32 divide by 2 7x=16 x=16/7, which is 2 and 2/7 ok maybe you typed that question wrong?
3. ### Algebra

2(3x - 7) + 4 (3 x + 2) = 6 (5 x + 9 ) + 3 how will solve it?
4. ### Math

The problem to solve is: (x+20)(x-12)(x+4)>0 but I can't figure out how to do this right so I left off the >0 and tried to solve the equation. x+20 evaluates to x+20 x-12 evaluates to x-12 Multiplying x+20 by x-12 is a classic …
5. ### Algebra

((k^2+6k+9)/(k^2+12k+27))×(k^2+9)/((k^2+12k+27)) express in lowest terms
6. ### Algebra - for bobpursley

Problem given: 14-4(2k+4) = -2(4-3k) 14-8k-16 = -8+12k -8k-2 = -8+12k plus 8k to each side ~~> -2 = -8+20k plus 8 to each side ~~>6 = 20k divide both sides by 20 ~~> 3/10 = k